Studies on blue mould rot of kinnow (Citrus reticulata) due to Penicillium italicum Wehmer in relation to temperature, relative humidity and biochemical parameter (Indian Journal of Arid Horticulture, 2025)
Five different post-harvest rots i.e. blue mould rot, green mould rot, sour rot, core rot and stem-end rot were prevalent in kinnow fruits during the survey period viz., December, 2009 to March, 2010 in fruit markets of Bikaner, Rajasthan. The blue mould rot was most predominant during February 1, 2010 to March 1, 2010. The average incidence of all the five rots studied ranged from 5.17 to 5.32 per cent during first fortnight of March, 2010. The cork-borer injury method of inoculation proved to be most effective in developing blue mould rot in kinnow fruits. The severity of blue mould rot was maximum at 25°C closely followed by 20°C. While, it was lowest at 30°C. The disease severity increased with the increase in relative humidity. It was highest at 100 per cent RH and lowest at 50 per cent RH. The levels of total soluble solids, acidity, ascorbic acid, total soluble sugar, reducing sugar and non-reducing sugar decreased in kinnow fruits with the increase in the severity of blue mould rot. Maximum reduction in total soluble solids, acidity, ascorbic acid, total soluble sugar, reducing and non-reducing sugars was observed in fruits having more than 75 per cent disease severity.
Keywords: Kinnow; blue mould rot; Penicillium italicum; temperature